THE POTENTIAL OF WATERMELON ALBEDO AS A RAW MATERIAL IN THE PRODUCTION OF SHEET JAM - Naya Septhiago; Zuhra Amalia; H Harunsyah (Politeknik Negeri Lhokseumawe, 2026)
Watermelon (Citrullus lanatus) is generally used for its flesh, while the white part of the rind (albedo) is rarely used and often becomes waste. Albedo contains high levels of pectin, making it suitable for processing into food products such as sheet jam, which is an innovative thin sheet of jam that is practical to serve. This study aims to determine the effect of variations in pectin concentration and heating time on the physical and organoleptic characteristics of watermelon albedo sheet jam. The experimental design used a two-factor factorial: pectin concentration (0.5%; 1%; 1.5%; 2%; 2.5%) and heating time (1, 3, 5, 7, 9 minutes) with 25 treatment combinations. The parameters observed included moisture content, pH, syneresis, hardness, and organoleptic properties (color, aroma, taste). The results showed that an increase in pectin concentration and heating time had a significant effect on reducing moisture content, increasing hardness, reducing syneresis, and altering sensory perception. The best treatment was found in the 2.0% pectin and 5-minute heating sample, producing a firm but not too hard texture (247 g), low syneresis (1.82%), moisture content of 17.79%, and pH of 4.7. Watermelon albedo has the potential as a raw material for sheet jam with the right pectin and heating formulation. Keywords: Heating Time, Pectin, Physical Characteristics, Sheet Jam, Watermelon Albedo